Enantioseparation and structural optimisation of b-lactams and stilbene analogues for the treatment of triple negative breast and chemoresistant colorectal cancers - McLoughlin, Eavan Ciara (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2023)
Triple negative breast cancer (TNBC) is characterised by an extremely aggressive clinical phenotype and minimal expression of typical breast cancer receptors such as the estrogen, progesterone or HER2 receptors.1, 2 Patient responses to endocrine and HER2 targeted therapies in TNBCs are poor, with pharmacological treatment options limited solely to chemotherapy. Colorectal cancer (CRC) is the third most frequently diagnosed cancer and cause of cancer related deaths worldwide. Despite introduction of targeted therapies, survival rate remains only 12% and only 50% of patients respond to treatment. Cis stilbene combretastatin A-4 (CA-4) has demonstrated excellent antimitotic and anticancer activity as a microtubule depolymeriser and colchicine binding site inhibitor (CBSI). The cis stilbene structure is 60 times more active as an anti-proliferative agent than the corresponding trans CA-4. However the active cis conformation readily isomerises into the less active trans isomer during storage and in vivo metabolism. Introduction of a rigid b- lactam structure in place of CA-4?s stilbene bond has been achieved by our group over the last decade as a strategy of cis restriction. This overcomes undesirable cis to trans isomerisation. This chemistry has garnered a large panel of the most potent microtubule destabilising agents reported to date, known as `the combretazets?. b-lactam derivatives of CA-4 have only been evaluated to date in vitro in their racemic forms. This thesis therefore is focused on enantioseparation, characterisation and biochemical evaluation of the enantiopure combretazets. Optimisation of diastereomeric chiral resolution (DR) for enantioseparation of each enantiomer within the b-lactam racemates using amino acid chiral derivatising reagents diastereomer forms has therefore been explored. These enantiomers are structurally designed specifically for dual activity in colorectal and breast cancer cells. A quantitative (q) NMR technique was developed and validated for determining diastereomeric excess following diastereomeric chiral resolution. Chiral resolution proved as a sufficient approach to achieve racemate enantioseparation, yielding up to 95% enantiomeric excess (ee). Subsequent biochemical evaluation in a panel of breast cancer, HL-60 human leukaemia and CA-4 resistant HT-29 colorectal cancer cells, determined that the 3S,4S of the 3-hydroxyl panel and 3S,4R of the 3-substituted panel are the optimal absolute configurations for maximal anti-proliferative, microtubule destabilising and anti-mitotic activity as the eutomers of racemic enantiomer pairs. Kinetic enzymatic resolution (KR) as a biocatalytic approach for enantioseparation of b-lactam racemates was also explored to afford a more accessible, sustainable and greener enantioseparative approach. Enantiomers were isolated with ee values between 70-99%.Additionally, b-lactam synthesis of the trans stilbene anti-angiogenic P3 structure was explored, employing a pyrazine A ring in place of CA-4?s 3,4,5-trimethoxyphenyl A ring and additionally the b-lactam method for cis restriction. The P3 pyrazet b-lactam 151, isolated in this thesis had superior anti-proliferative activity compared to parent P3 in a panel of cancer cell lines. This demonstrates potential scope of A ring modifications in order to preserve anti-proliferative activity and illustrates that b-lactam ring insertion has potential to augment bioactivity. In summary, the agents described in this thesis offer potential strategies for future curative and effective management of resistant, advanced and metastatic breast and colorectal cancers and are therefore worthy of further development.
APPROVED